2020
DOI: 10.1111/exsy.12550
|View full text |Cite
|
Sign up to set email alerts
|

Contracting in Brazilian public administration: A machine learning approach

Abstract: The risk of non-fulfilment of a contract can harm public administration or even interrupt public services. Therefore, models that assist manager decision making in the audit and control of contracts with a higher disqualification risk may be important tools, with economic and even social repercussions. In this article, public contracts are classified with respect to the risk of non-compliance with their terms of delivery. The quantitative tools used are statistical and machine learning models, similar to credi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
4
0
2
Order By: Relevance
“…The most influential authors in a research area can be identified using indicators that measure their influence on a given theme from the number of published works [50]. The h-index proposed by Hirsch [51] is defined by the largest number h of papers by an author that received at least h citations.…”
Section: Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The most influential authors in a research area can be identified using indicators that measure their influence on a given theme from the number of published works [50]. The h-index proposed by Hirsch [51] is defined by the largest number h of papers by an author that received at least h citations.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…In addition, Lotka's law, which indicates an inverse exponential scale of the number of articles per author, can be used to further measure scientific productivity. Few authors tend to publish a large number of articles in a given area of knowledge while most authors publish a small number of papers [50]. Potter [55] pointed out that, when there is a coverage period of 10 years or more, Lotka's law can be a useful metric.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…The proposed model would help reduce the obsolete inventory using information technology in market-oriented procurement planning to match the demand and supply efficiently. Henrique et al (2020) argued that the risk of incompletion of contract might be responsible for a low public services' delivery. Therefore, the administrative bodies should conduct the audit and checks on the contractors to reduce the risk of non-compliance.…”
Section: International Contextmentioning
confidence: 99%
“…Uma cifra considerável a qual não está livre de possíveis riscos, tais como, erro processual na descrição correta do item, falha na entrega, corrupção, quarteis, etc. e mitigar esses riscos é um desafio para o gestor público que objetiva realizar a melhor comprar (Henrique et al, 2020;Yazdani et al, 2019;Aghajanian, 2018;Cortis et al, 2018;Hyari, 2017;Mysiak & Dionisio Pérez-Blanco, 2016). Assim, o papel das compras públicas no desenvolvimento sustentável emerge de uma grande discussão nos últimos anos devido à sua participação nos gastos públicos (Zaidi et al, 2019;Brammer & Walker, 2011).…”
Section: Introductionunclassified